Practical feasibility of a high-precision 3-UPU parallel mechanism. Issue 3 (May 2014) - Bhutani, Gaurav; Dwarakanath, T. A.
SUMMARY In this paper, we revisit the 3-degrees of freedom (DOF) pure translational mechanism. The mathematical model and the design considerations are discussed. A detailed sensitivity and error analysis is carried out and the results are discussed in a new perspective. The feasibility of the practical 3-DOF pure translational mechanism is established with novel design considerations to take care of theoretical mobility and geometrical constraints. We describe and validate the theoretical observations with stage-wise prototype models and experiments. The experimental results concur that all is well with 3-UPU in contrast to what is presented in refs. [6, 9, 10].